Effect of non-uniform magnetic field on radial oscillation of electron beam in a low-magnetic-field foilless diode. (16th June 2022) - Zhang, Guangshuai; Sun, Jun; Wu, Ping; Shi, Yanchao; Fan, Zhiqiang; Hua, Ye; Tan, Nongchao
Abstract: A theory regarding a non-uniform magnetic field with a parallel gradient is presented. The research results show that a proper non-uniform magnetic field can greatly reduce the transverse momentum of an electron beam and even eliminate its gyration motion, and it depends on the gradient of the magnetic field and the phases of electrons entering and leaving the local magnetic field region. Thus, a magnetic field that decreases along the axial direction is proposed to suppress the radial oscillation of the electron beam. However, in the drift tube, the suppression of the radial oscillation is not obvious, because the large phase differences among electrons lead to a mismatch between the electron beam and the non-uniform magnetic field. Further studies found that the non-uniform magnetic field applied in the anode-cathode gap can not only reduce the phase differences among electrons, but also effectively transform the transverse momentum of the electron beam into its axial momentum. The results obtained by PIC simulations and experiments consistently confirm that the non-uniform magnetic field can significantly suppress the radial oscillation of the electron beam in a low-magnetic-field foilless diode.